Proximate Composition and Sensory Properties of Ukpo oka: A Steamed Maize Pudding Formulated from Maize and African Yam Bean Flour - Chidi, Anosike Francis; Ekene, Nwagu Kingsley; Francis, Ekwu; Nwalo, Nweke Friday; Theophilus, Nwoba Sunday; Nkechinyere, Onuegbu Rosemary; Nwakaego, Enwere Evelyn (Pakistan Journal of Nutrition, 2019)
Background and Objective: The proximate and sensory properties of supplemented food products determine their acceptability. Ukpo oka (a steamed maize pudding) as a cereal product is generally low in protein content thus requiring supplementation from other food sources like African yam bean. Supplementing ukpo oka with African yam bean may likely improve the nutritional content of Ukpo oka and help solve the problem of protein-energy malnutrition and hidden hunger. This study was designed to determine the effect of supplementing maize flour with African yam bean flour based on the proximate composition and sensory properties of Ukpo oka. Materials and Methods: Mixtures of processed maize flour and African yam bean flour were formulated in the ratios of 100:0, 50:50, 80:20, 60:40, 20:80, respectively to produce Ukpo oka. Proximate composition and sensory properties of the products were determined according to the method of the Association of Official Analytical Chemist and Iwe, respectively. Results: The protein (3.91-11.08%), ash (2.90-6.60%) and fiber (0.67-1.82%) content of the flour blends increased with addition of African yam bean flour while carbohydrate content of maize-African yam bean flour blends decreased with increase in the level of African yam bean flour. Flour blend 100:0 had the highest energy value while flour blend 20:80 had the least energy value. Sensory evaluation of products revealed that the products were highly rated in all sensory attributes. Flour blend 50:50 was the most preferred in terms of general acceptability. Conclusion: The study showed that poor nutritional quality of ukpo oka can be improved through supplementation with African yam bean. It can serve as a high nutritious and energy given food that is accepted at household level.